Methodical approaches and statistical analysis of tourist arrivals to the centers of sightseeing tourism (on the example of Chernivtsi, Ukraine) - Krul, Halyna; Korol, Oleksandr; Zaiachuk, Oksana; Kostash, Mykola (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, Kraków, 2023)
In many countries of the modern world, the tourism industry occupies one of the leading positions, significantly contributing to their economy and promoting the socio‑economic development and living standards of each tourist‑attractive region. One of the principal types of tourism is considered to be sightseeing or cultural tourism. Objects recognized and included in the UNESCO World Heritage List hold particular significance for tourists. Their presence in a certain territory significantly increases the interest of both foreign and domestic tourists not only in the landmark itself but also in the destination as a whole.Chernivtsi is renowned as one of the prime hubs for sightseeing tourism in Ukraine. Tourists are attracted to the city’s historic center, which was formed during its inclusion in the Austro‑Hungarian Empire. The inclusion of the Chernivtsi National University (for‑merly the Residence of Bukovinian and Dalmatian Metropolitans) in the UNESCO World Heritage List on June 28, 2011, significantly heightened the appeal of this destination among tourists. This example shows how inscribing a site on the World Heritage List can influence the dynamics of tourist arrivals. It is also scientifically intriguing to analyze the effects of both global factors, such as the COVID‑19 pandemic, and regional factors, like the annexation of Crimea by Russia in 2014, on the dynamics of tourist arrivals to sightseeing tourism centers such as Chernivtsi.
Keywords: methodology of tourism flow accounting; sightseeing tours and excursions; sightseeing visits; tourism and UNESCO sites